Customer Experience as a Strategic Driver of Value Creation in Entrepreneurial Marketing - Hery Margono (Global Writing Academica Researching and Publishing, 2024)
Changing business dynamics and increasing competition are driving businesses to focus not only on products or services but also on the customer experience in every interaction. In the entrepreneurial context, flexible, personalized, and proximity-based interactions are characteristics that influence how customers perceive the value they receive. The complexity of interactions involving multiple channels and increasing customer expectations demands more adaptive and targeted experience management. This study aims to examine the role of customer experience as a strategic driver of value creation in entrepreneurial marketing practices. This research uses a qualitative approach, utilizing various relevant secondary data sources for in-depth analysis. The results indicate that customer experience plays a significant role in shaping value perceptions through interaction quality, emotional engagement, and the consistency of the experience. Furthermore, business actors' responsiveness in adjusting interaction strategies and their ability to manage resource constraints are crucial factors in maintaining the relevance of the customer experience. Overall, the integration of customer experience into entrepreneurial marketing strategies has strategic implications for supporting business sustainability, building loyalty, and creating differentiation amidst increasingly dynamic competition.